The influence of celebrity endorsers on the hog feeds industry: A study on backyard hog raisers consumer buying behavior - Escondo, Clint B. (Animo Repository, 2017)
Today, celebrity endorsements have become one of the most lucrative industries in the world. Marketers tap celebrities to endorse their brand/s to satisfy their overall brand strategy, hoping to eventually influence their target consumers to buy their brand/s. This research study will focus on celebrity endorsement and its impact on the consumer buying behavior specifically on backyard hog raisers. The study will also gauge the relationship of the level of celebrity endorser credibility and level of celebrity endorser advertising effectiveness to the hog raisers purchase intent.